2022
DOI: 10.1097/bpo.0000000000002090
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Rebound Phenomenon After Temporary Hemiepiphysiodesis and Implant Removal for Idiopathic Genu Valgum in Adolescent Patients

Abstract: Background: The aim of this study was to investigate factors determining postoperative courses, especially focusing on the rebound phenomenon, in adolescent patients with idiopathic genu valgum who underwent temporary hemiepiphysiodesis and implant removal. Methods: We identified and reviewed patients with idiopathic genu valgum treated with temporary hemiepiphysiodesis [using tension-band plates (plate group, PG) or transphyseal screws (screw group, SG)] and followed-up to skeletal maturity. Results: In our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Baghdadi et al reported 0.52°/month with plates 30 . In studying valgus deformity, Ko et al observed that screws achieved 0.65° ± 0.25°/month and plates, 0.71° ± 0.23°/month, but the plate group showed greater occurrence of rebound while the screw group showed progressive genu varum after implant removal 31 . Park et al reported a rate of correction of 0.92°/month with screws and 0.64°/month with plates 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baghdadi et al reported 0.52°/month with plates 30 . In studying valgus deformity, Ko et al observed that screws achieved 0.65° ± 0.25°/month and plates, 0.71° ± 0.23°/month, but the plate group showed greater occurrence of rebound while the screw group showed progressive genu varum after implant removal 31 . Park et al reported a rate of correction of 0.92°/month with screws and 0.64°/month with plates 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of unmatched cohorts have suggested that screws may effect change more rapidly 18,20,21 . The authors of another study disagreed 31 ; however, that study did not observe MAD as an outcome. Since the first use of TS and GMP in studies published in 1998 3 and 2007 2 , respectively, much of the literature suggests that postoperative complications appear similar between the 2 methods 5-12 .…”
Section: Comparison Between Screws and Platesmentioning
confidence: 94%
“…Deformity recurrence after implant removal, or the so-called rebound phenomenon, is a highly expected complication in the correction of the coronal plane deformities of the knee. 5 Although there is no uniform definition for this phenomenon, risk factors associated with deformity recurrence were studied in several publications [3][4][5]7,[13][14][15][16] proper methods to overcome this and their outcomes, however, were poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Male gender, a younger age at the time of the surgical procedure, a shorter duration of retention of implants, and overcorrection of deformity were identified as risk factors for the occurrence of rebound deformity of at least 3° in patients with genu valgum due to skeletal dysplasia who were treated with tension band plates 55 . The results of another study revealed a higher incidence of rebound with faster correction speeds and following tension band plating for growth modulation compared with transphyseal screw hemiepiphysiodesis 56 . Gerges et al reported a 36% rebound rate and a 16% incidence of tethering and undesired continuation of growth modulation in a cohort of patients in whom a guided-growth implant for angular deformity correction around the knee had been converted to a sleeper plate by removal of the metaphyseal screw 57 .…”
Section: Guided Growthmentioning
confidence: 96%